The NLRP3 Inflammasome Is Upregulated in HIV-Infected Antiretroviral Therapy-Treated Individuals with Defective Immune Recovery - Bandera, Alessandra; Masetti, Michela; Fabbiani, Massimiliano; Biasin, Mara; Muscatello, Antonio; Squillace, Nicola; Clerici, Mario; Gori, Andrea; Trabattoni, Daria (Frontiers in Immunology, 2018)
Background: Inflammasome-mediated activation of caspase-1 regulates inflammatory responses and pyroptosis. We analyzed possible associations between inflammasome-related genes and immune reconstitution in HIV-infected antiretroviral therapy (ART)-treated patients. Methods: Cross-sectional, case-control study. HIV-infected patients on ART for ≥24 months with HIV-RNA<50 cp/mL for ≥12 months were enrolled and defined as immunological responders (IR) or non responders (INR) if CD4 count was ≥500 or ≤350 cells/µL, respectively. Expression of inflammasome genes, caspases 1, 3, 4, 5 and γ-interferon-inducible protein 16 (IFI16) was measured in unstimulated and LPS- or aldrithiol-2-treated HIV-1BaL virions-stimulated PBMCs. Microbial translocation markers were evaluated. Results: Thirty-nine patients (22 IRs; 17 INRs) were enrolled. LPS-stimulated inflammasome genes were significantly upregulated in INRs. Whereas HIV-1BaL stimulation induced Nod-Like-Receptor-3 (NLRP3) expression in both IRs and INRs, NLRP3 and IL-18 expression was significantly increased in INRs compared to IRs. Significant higher caspase-1 expression was seen as well, whereas caspase 3, 4 and 5 expression was similar in both groups. No differences in microbial translocation markers (LPS and sCD14) was detected in the two groups. Conclusions: Upregulation of NLRP3 and caspase-1 is observed in INR patients. This could play a role in persistent immune activation that characterize INRs. Caspase-1 upregulation could induce CD4 T-cell loss via pyroptosis, contributing to unsatisfactory CD4 T-cells recovery.